2016
DOI: 10.1038/srep38717
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphic function of IL-17 in salivary gland dysfunction of the C57BL/6.NOD-Aec1Aec2 model of Sjögren’s syndrome

Abstract: Interleukin (IL)-17 is one of the critical inflammatory cytokines that plays a direct role in development of Sjögren’s syndrome (SjS), a systemic autoimmune disease characterized by a progressive chronic attack against the exocrine glands. The expression levels of IL-17 are correlated with a number of essential clinical parameters such as focus score and disease duration in human patients. Significantly immunological differences of Th17 cells were detected at the onset of clinical disease in female SjS mice co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 56 publications
3
38
0
Order By: Relevance
“…Remarkably, the IL-17R expression levels are also elevated in the glandular ducts of patients with SS [ 98 ]. These results in SS patients are also supported by similar findings in mouse models of SS, in which systemic and local levels of IL-17, as well the frequency of Th17 cells, are elevated in the salivary and lacrimal glands of these mice [ 99 , 100 , 101 ]. In addition, it has been found that cytokines that promote Th17 differentiation, such as TGF-β, IL-6 and IL-23, are also elevated in SS patients [ 90 ].…”
Section: Il-17 In Systemic Rheumatic Diseasessupporting
confidence: 78%
“…Remarkably, the IL-17R expression levels are also elevated in the glandular ducts of patients with SS [ 98 ]. These results in SS patients are also supported by similar findings in mouse models of SS, in which systemic and local levels of IL-17, as well the frequency of Th17 cells, are elevated in the salivary and lacrimal glands of these mice [ 99 , 100 , 101 ]. In addition, it has been found that cytokines that promote Th17 differentiation, such as TGF-β, IL-6 and IL-23, are also elevated in SS patients [ 90 ].…”
Section: Il-17 In Systemic Rheumatic Diseasessupporting
confidence: 78%
“…Because IL-17A is a pro-inflammatory cytokine, its dysregulation is associated with various autoimmune disorders, such as type 1 diabetes, rheumatoid arthritis, and Sjögren’s syndrome 23 25 . Furthermore, our data support previous findings that patients with active AA had elevated IL-17 concentrations 15 , 16 , and suggest that IL-17 may also play a role in AA progression.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps even more interesting is the observation, first made in C57BL/6.NOD- Aec1Aec2 mice, then soon after in humans [31], indicating the presence of IL-17-producing CD4 + T H 17 cells in the salivary glands of both species diagnosed with SS/SS-like disease. Since then, an increasing number of mouse models of SS-like disease are reporting the presence of T H 17 cells in the glands [32,33], which may prove pivotal in SS following the recent publications of Nguyen et al [34,35] suggesting differential responses of cells in male versus female C57BL/6.NOD- Aec1Aec2 mice and human SS patients to IL-17. This observation, combined with the detection of reduced IL-2 production, first described in NOD mice [36], have focused attention on the importance of the innate inflammatory response in both murine and human SS diseases that now must be analyzed fully and defined molecularly.…”
Section: What Have We Learned About Ss From Mouse Models Of Ss-likmentioning
confidence: 99%